2023
DOI: 10.3390/ijms24032500
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study between Lycorine and Galantamine Abilities to Interact with AMYLOID β and Reduce In Vitro Neurotoxicity

Abstract: Galantamine is a natural alkaloid extracted from the Amaryllidaceae plants and is used as the active ingredient of a drug approved for the treatment of the early stages of Alzheimer’s disease. It mainly acts as an acetylcholinesterase (AChE) inhibitor, increasing concentrations of the acetylcholine neurotransmitter. Recent cellular studies have also shown the ability of galantamine to protect SH-SY5Y cell lines against amyloid-β (Aβ)-induced toxicity. Such investigations have supported and validated further in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 82 publications
4
10
0
Order By: Relevance
“…All identified pairs are listed in Supplementary Table S5 and detailed descriptions of selected pairs are provided in the Supplementary Materials (Results—Identifying the Most Similar Chemical for each Nanomaterial Based on their Mechanism of Action). For example a copper oxide nanomaterial was found to act similar to Lycorine and both have been shown to affect acetylcholinesterase and in result the nervous system ( Sezer Tuncsoy et al 2019 , Kola et al 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…All identified pairs are listed in Supplementary Table S5 and detailed descriptions of selected pairs are provided in the Supplementary Materials (Results—Identifying the Most Similar Chemical for each Nanomaterial Based on their Mechanism of Action). For example a copper oxide nanomaterial was found to act similar to Lycorine and both have been shown to affect acetylcholinesterase and in result the nervous system ( Sezer Tuncsoy et al 2019 , Kola et al 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aβ peptides have been identified as the cause of dendritic degeneration and loss of synapses, which ultimately leads to neuronal death in the rat hippocampus . Additionally, in vitro studies using cells from PC12 cells (rat pheochromocytoma , and SH-SY5Y cells) , (human neuroblastoma) have demonstrated that extracellular fibrillar aggregates of Aβ peptides are neurotoxic. However, these cells are unsuitable for neurodegenerative disease research due to their instability and inability to create a diverse population of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ peptides have been identified as the cause of dendritic degeneration and loss of synapses, which ultimately leads to neuronal death in the rat hippocampus. 12 Additionally, in vitro studies using cells from PC12 cells (rat pheochromocytoma 14,15 and SH-SY5Y cells 16,17 (human neuroblastoma) have demonstrated that extracellular fibrillar aggregates of Aβ peptides are neurotoxic. However, these cells are unsuitable for neurodegenerative disease research due to their instability and inability to create a diverse population of neurons.…”
Section: Discussionmentioning
confidence: 99%